CENTRAL ASIA AND CHINA: NEW HORIZONS OF INTERNATIONAL REGIONALIZATION - GALIAMOVA, Venera (CENTRAL ASIA AND THE CAUCASUS, 2007)
Central Asia is currently a hot item on the global agenda. It is not every decade that the world finds itself embracing a new region with the alluring appeal of mass hydrocarbon production and export, large investments, and promising cooperation in the military sphere. What is more, other phenomena adding to Central Asia’s renown are intensifying the glow of the geopolitical theme.hey include the local governments’ opposition to the extremist movements, the West’s accusations of authoritarianism and violations of democratic rights and freedoms, the Islamic renaissance, the Color Revolutions, and so on. In addition, it is obvious that the West is keeping a sharp eye on the region’s republics, which is shown by its immediate reaction to the events going on in Central Asia, whereby this attention continues to increase all the time.1 Emissaries not only from Western, but also from many other large countries are actively working in the region. There must obviously be extremely good reasons why even the most distant centers of power are showing such an intense interest in Central Asia. And the answers lie deeper than they appear to at first glance. The domestic sociopolitical evolution of the Central Asian states is of little interest to most for-eign observers. As paradoxical as it may seem, the problem of drug trafficking, which is pertinent to the Central Asian Region (CAR) and urgent for the whole world, is being studied even less. In this case, the priority topics for political analysis—apart from big business issues (read: the production of natural resources)—are the Big Game being waged among the leading present-day nations over the region, Russia’s strategy in Central Asia, and the spread of China’s influence there, which are all closely associated with CAR. In short, we are talking about geopolitical rivalry in the region. It is clear to many that oil and gas cannot be the only reason for this excitement. For as long as hydrocarbons are being produced and are in demand, they will always reach their consumer, whereby these resources will be transported via profitable, and not politically advantageous, routes—this is a law of economics, the violation of which is fraught with serious consequences, primarily for the exporter state. It stands to reason that it is not Kazakhstan that needs new pipelines, but other states that need guaran-teed oil deliveries. The Central Asian Region was and largely remains dependent on Russia—essentially 100% of the strategic hydrocarbon resources produced here are transported through the Russian Federation.Only Kazakhstan, which is also linked to Moscow by a pipeline system, retains relative independence over its energy policy. It is likely that the development of the southern and trans-Caspian vectors of energy resource deliveries from Central Asia may indeed prove more profitable compared with the existing ones. However, this will not happen in the foreseeable future while chaos reigns in Afghanistan, Pakistan is being shaken from the inside, and the Caucasus is under permanent threat due to the absence of a normal dialog between Iran and the West. What is more, the current level of scientific developments will not permit putting the Caspian ecosystem at risk. Even if they are implemented soon, the numerous new transportation projects—those already carried out and only just being developed (West Kazakhstan-China, Baku-Tbilisi-Ceyhan, Turkmenistan-China, Uzbekistan-China, Nabuc-co)—will nevertheless be incapable of radically changing the situation in the midterm with respect to energy deliveries from the region. In all likelihood, the insistent attempts to diversify energy export from Central Asia are simply aimed at undermining Russia’s domination in the region.2 Possible annual deliveries of energy resources in amounts of up to several tens of thousands of tons or millions of cubic meters bypassing the Russian Federation may be detrimental not so much to Russia’s economic, as to its strategic interests. On the whole, the questions relating to the production and transportation of energy resources are only partially raising the veil to reveal what is hidden behind the geopolitical game in Central Asia, what its rules are, and what prize the winner will receive. In our opinion, raising of the problem of international regionalization could provide a more in-depth explanation of the current situation in Central Asia.